The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.7717/peerj.7747
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing gene tree conflict in plastome-inferred phylogenies

Abstract: Evolutionary relationships among plants have been inferred primarily using chloroplast data. To date, no study has comprehensively examined the plastome for gene tree conflict. Using a broad sampling of angiosperm plastomes, we characterize gene tree conflict among plastid genes at various time scales and explore correlates to conflict (e.g., evolutionary rate, gene length, molecule type). We uncover notable gene tree conflict against a backdrop of largely uninformative genes. We find alignment length and tree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
101
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 125 publications
(186 reference statements)
13
101
2
Order By: Relevance
“…Interestingly, it has been suggested that Hosta and Yucca have a relatively closer affinity in the Liliaceae, although Hosta was previously considered to belong to the Liliaceae (Hutchinson 1959, Cronquist 1981 or Funkiaceae (Dahlgren et al 1985). Previous studies have suggested different topologies for the Liliaceae family, plausibly because of actual conflicting signals from methods or models (Hutchinson 1959, Cronquist 1981, Dahlgren et al 1985, Walker et al 2019. In summary, we obtained consistent results in our phylogenetic analyses based on the complete cp genomes and protein-coding sequences, which makes our conclusions more reliable and convincing.…”
Section: Phylogenetic Relationshipssupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, it has been suggested that Hosta and Yucca have a relatively closer affinity in the Liliaceae, although Hosta was previously considered to belong to the Liliaceae (Hutchinson 1959, Cronquist 1981 or Funkiaceae (Dahlgren et al 1985). Previous studies have suggested different topologies for the Liliaceae family, plausibly because of actual conflicting signals from methods or models (Hutchinson 1959, Cronquist 1981, Dahlgren et al 1985, Walker et al 2019. In summary, we obtained consistent results in our phylogenetic analyses based on the complete cp genomes and protein-coding sequences, which makes our conclusions more reliable and convincing.…”
Section: Phylogenetic Relationshipssupporting
confidence: 83%
“…wabuensis with 100% bootstrap support, as also previously indicated (Lan et al 2018). Previous studies have suggested different topologies for the Liliaceae family, plausibly because of actual conflicting signals from methods or models (Hutchinson 1959, Cronquist 1981, Dahlgren et al 1985, Walker et al 2019. 6, Supplementary material Appendix 1 Fig.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Eight of the top 10 markers are more than 900 bp, indicating that longer genes are superior for phylogeny reconstruction, as previous suggested by Walker et al (2019), although they may require internal primer designing for complete Sanger's sequencing. A list of the top 10 markers with less than 900 bp is reported (Table S5), and primer pair design for the top five is provided in Table 4.…”
Section: Phylogenetically Informative Regionsmentioning
confidence: 52%
“…Gonçalves et al (2019) emphasized the importance of considering variation in phylogenetic signal across plastid genes and the exploration of plastome data to increase accuracy of estimating relationships; they also revealed that phylogenies inferred with multispecies coalescent (MSC) methods are accurate with plastome matrices and should be considered in future phylogenomic investigations. Walker et al (2019) highlighted that most genes are largely uninformative and are unlikely to misguide plant systematics. However, the concatenating of plastid genes without some level of scrutiny can mislead branch length estimation .…”
Section: Phylogenetically Informative Regionsmentioning
confidence: 99%
See 1 more Smart Citation